Comparative analysis of scalar based SVPWM techniques for open end winding induction motor drive - Madhuri, B; Ranjit, M; Ramesh Babu, V; Srinivasa Rao, J (International Journal of Engineering and Technology, 2018)
In thiswork, scalarbased SVPWM techniquesare implemented fordual inverterfed open end winding induction motor (IM) drive with single DC sourceand separate DC sources. To reduce the common modevoltage and to reduce the switching loss in conventional two level three phase voltage source inverter (VSI), scalar based SVPWM techniques are implemented for dual inverter configuration. By using thisscalarbased approach various discontinuous or Non-Centric PWM techniques are obtained with the addition of zero sequence signal to the reference phasevoltage.Whereasin conventional SVPWM technique, it requirescalculation of sector identification and look up tableswhich iscumbersome. In Non-centric PWM techniqueseach phase isclamped to atmost 120 degreesforevery fundamental voltage cycle, which helps in reducing the switching losses. To validate the proposed work numerous simulations have been performed on both proposed configurations using MATLAB/SIMULINK environment and simulation results are presented and compared for both proposed models.Â Â Â